Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1046/j.1524-4733.2001.004001016.x
|View full text |Cite
|
Sign up to set email alerts
|

A Multinational Pharmacoeconomic Evaluation of Acute Major Depressive Disorder (MDD): a Comparison of Cost-Effectiveness Between Venlafaxine, SSRIs and TCAs

Abstract: Within the inpatient and outpatient treatment settings, venlafaxine IR was a more cost-effective treatment of MDD compared to the SSRIs and TCAs. Additionally, the results of this investigation indicate that increased utilization of venlafaxine in most settings across Europe and the Americas will have favorable impact on health care payer budgets. ADR, adverse drug reaction; CMA, clinical management analysis; ECT, electroconvulsive therapy; HAM-D, Hamilton Depression Scale; MADRS, Montgomery-Asberg depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 25 publications
1
26
0
1
Order By: Relevance
“…67 Direct and indirect costs in the United States are estimated to be as high as 80 billion dollars per year. 68 Response rates to conservative management with FDA-approved antidepressants range from 45-55%, and remission rates can be as low as 30%. Although polytherapy may benefit some individuals, electroconvulsive therapy (ECT) has been associated with the highest remission rates.…”
Section: Vagus Nerve Stimulation For Treatment-resistant Depressionmentioning
confidence: 99%
“…67 Direct and indirect costs in the United States are estimated to be as high as 80 billion dollars per year. 68 Response rates to conservative management with FDA-approved antidepressants range from 45-55%, and remission rates can be as low as 30%. Although polytherapy may benefit some individuals, electroconvulsive therapy (ECT) has been associated with the highest remission rates.…”
Section: Vagus Nerve Stimulation For Treatment-resistant Depressionmentioning
confidence: 99%
“…The majority of these use decisionanalytic techniques and are based on secondary data. 18,[70][71][72][73][74][75][76][77] Only three evaluations collected resource-use and outcome data within the studies, of which two studies collected data prospectively alongside clinical trials. [78][79][80] Of the evaluations using decision-analytic techniques to evaluate the cost-effectiveness of these medications in outpatients or primary care, the majority found in favour of SSRIs.…”
Section: Previous Work On the Costeffectiveness Of Antidepressant Drugsmentioning
confidence: 99%
“…Their results for outpatient settings suggested that SSRIs dominated TCAs in eight countries, including the UK, but produced additional benefit at a cost in two countries. 74 Einarson and colleagues found that SSRIs dominated TCAs when compared in an outpatient setting, but that TCAs dominated SSRIs when compared in an inpatient setting. 76 Results from a study by the Canadian Co-ordinating Office for Health Technology Assessment (CCOHTA) suggested that first line treatment (allowing for switching) with SSRIs produced a QALY gain at an additional cost compared with first line treatment with TCAs.…”
Section: Previous Work On the Costeffectiveness Of Antidepressant Drugsmentioning
confidence: 99%
“…In almost all studies, venlafaxine or SNRIs were cost-effective compared to SSRIs and TCAs (9,13,18). A recent Brazilian study concluded that SNRIs, SSRIs, and TCAs had no significant differences in cost-effectiveness results (19).…”
Section: Discussionmentioning
confidence: 99%
“…Most pharmacoeconomic studies on antidepressants have been conducted in Europe and North America, however, with only a few analyses of this type performed in South America (7,8). Only one study (in Venezuela) was found evaluating antidepressants (9). There were three existing pharmacoeconomic studies available in Colombia (7).…”
mentioning
confidence: 99%